A SINGLE METASTATIC LARGE ADRENAL MASS MIMICKING ADRENOCORTICAL CELL CARCINOMA - WH, Wan Mohd Hafez; MA, Masliza Hanuni; WA, Siti Sanaa; Mohamad, Hussain; Muda, Nor Hisham (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Invasive breast ductal carcinoma commonly metastasizes to the lungs, liver, bones and brain. Solitary adrenal metastasis from invasive ductal carcinoma is extremely rare. Hence, a single large adrenal metastasis can mimic a primary adrenal tumour such as adrenocortical carcinoma. We report a case of a rare single metastatic large adrenal mass from invasive ductal carcinoma mimicking adrenocortical carcinoma. CASE A 49-year-old female, with a known case of invasive ductal carcinoma of the right breast underwent right mastectomy and axillary clearance and completed 6 cycles of systemic chemotherapy and 15 cycles of radiotherapy. The FDG-PET scan surveillance post-treatment showed FDG-avid left adrenal mass suggestive of metastasis or primary malignancy with no other solid organ or bone metastasis. Subsequent computed tomography (CT) scan also showed a large, irregular lobulated solid left adrenal mass measuring 7.3 x 4.8 x 5.4 cm. Plain HU was 30 HU and the calculated absolute washout was 55%. A large left adrenal mass with the absence of other solid organs and bone metastasis made adrenocortical carcinoma one of the possible aetiologies. Biochemical investigation to assess adrenal tumour functionality, namely, overnight dexamethasone suppression test (ODST), aldosterone renin ratio (ARR) and 24-hour urine metanephrines all yielded normal results. Left open adrenalectomy was performed and histopathological examination (HPE) confirmed left adrenal metastasis from the breast carcinoma. CONCLUSION Single large solitary adrenal metastasis from invasive breast ductal carcinoma is rare and can mimic adrenocortical carcinoma. Early recognition and adrenalectomy will probably lead to improved patient survival.